Assessing long-term energy security: The case of electricity in the United Kingdom. (February 2018) - Cox, Emily
Abstract: There is a growing body of research into the potential security risks and trade-offs which may emerge over the long-term development of energy systems. As part of this body of research, this paper aims to develop and demonstrate a set of indicators for assessing the security of long-term national electricity scenarios. This paper extends the empirical work of existing frameworks by including reliability and cost parameters alongside a range of other important aspects of energy security such as diversity, trade and acceptability, and by using both qualitative and quantitative indicators without aggregation in order to identify trade-offs. This paper uses the indicators to assess the energy security implications of three plausible long-term scenarios for the UK electricity system. The results indicate that a major risk may be experienced by a lack of flexible, responsive supply capacity in low-carbon electricity pathways. Reducing overall energy demand is found to be the most beneficial policy for improving energy security in terms of generating benefits in multiple dimensions. The paper finds that energy security is often conceptualised as the avoidance of causes of insecurity (such as insecure fuel imports), but that an equally important aspect of security lies in maximising responses to insecurity, for example by increasing the flexibility and responsiveness of both supply and demand.